2017
DOI: 10.1177/1461444817712723
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting #Ferguson: Mediatized fields and the new activist journalist

Abstract: As a hybrid, journo-activist space, tweeting #Ferguson quickly emerged as a way for activists and journalists to network and spread information. Using a mixed-methods approach combining digital ethnographic content analysis with social network analysis and link analysis, this study examines journalistic and activist uses of Twitter to identify changes in field relations and practices. Employing the lenses of field theory and mediatization, this study finds parity and divergence in the themes, frames, format, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 50 publications
1
24
0
1
Order By: Relevance
“…In our analysis of research that used Twitter data, we found a similar breadth of research topics, ranging from audience interactions around television shows (Boukes & Trilling, 2017;A. Williams & Gonlin, 2017) to social justice movements under hashtags such as #Ferguson (Barnard, 2018), and many political discussions around the world (Aelst, Erkel, D'heer, & Harder, 2017;Engesser, Ernst, Esser, & Büchel, 2017;Zelenkauskaite & Niezgoda, 2017;Zhang, Wells, Wang, & Rohe, 2017). Research topics were not limited to social and behavioral phenomena.…”
Section: Diversity Of Research Areasmentioning
confidence: 92%
“…In our analysis of research that used Twitter data, we found a similar breadth of research topics, ranging from audience interactions around television shows (Boukes & Trilling, 2017;A. Williams & Gonlin, 2017) to social justice movements under hashtags such as #Ferguson (Barnard, 2018), and many political discussions around the world (Aelst, Erkel, D'heer, & Harder, 2017;Engesser, Ernst, Esser, & Büchel, 2017;Zelenkauskaite & Niezgoda, 2017;Zhang, Wells, Wang, & Rohe, 2017). Research topics were not limited to social and behavioral phenomena.…”
Section: Diversity Of Research Areasmentioning
confidence: 92%
“…At the same time, that variety of research furnishes nuanced perspectives that enhance understanding of the evolving media system. Hybridity is often considered to be a mere convergence between structural different actors, like journalists and activists (Barnard, 2018), or journalists and programmers (Hermida and Young, 2017), convergence PRE-PRINT VERSION OF THE PAPER Delmastro, M., Splendore, S.. Google, Facebook and what else? Measuring the hybridity of Italian journalists by their use of sources.…”
Section: What Hybridity For a "Hybrid Media System"?mentioning
confidence: 99%
“…At the same time, that variety of research furnishes nuanced perspectives that enhance understanding of the evolving media system. Hybridity is often considered to be a mere convergence between structural different actors, like journalists and activists (Barnard, 2018), or journalists and programmers (Hermida and Young, 2017), convergence between reporting practices, or communication formats as among fictive and factual forms of storytelling (Baym, 2017), news and entertainment (Bailey, 2018) or news and advertising/public relations (PR; Erjavec, 2005). The notion of hybridity characterizes not only the cross-media flows of news, practices or professional roles, but also differentiations between producers and users of news (Harder et al, 2016; Papacharissi, 2015).…”
Section: What Hybridity For a ‘Hybrid Media System’?mentioning
confidence: 99%
See 1 more Smart Citation
“…Socialmovement research on and with Twitter has tended to focus on the techno-social capacity of the hashtag, Twitter's 'inline metadata' function that aggregates and organizes the multiplicity of tweets in trend patterns and 'ambient affiliations' among users (Zappavigna, 2011). See, for example, the numerous articles on the 2014 Ferguson riots, that ensued on the police killing of Michael Brown, which are based on statistical analysis of the hashtag '#Ferguson' (Barnard, 2018). It is all the more striking, then, that the publishers of Baltimore Uprising proceeded in their Twitter search, conducted during the course of the riots, by excluding trending hashtags, instead homing in on local landmarks, malls, high-school proms, store names, and idiosyncrasies of the riots.…”
Section: An Epistolary Of Tweetsmentioning
confidence: 99%